Response of the cerebral vasculature to systemic carbon monoxide administration—Regional differences and sexual dimorphism. (9th April 2020) - Oliveira, Sara R.; Castelhano, João; Sereno, José; Vieira, Helena L. A.; Duarte, Carlos B.; Castelo‐Branco, Miguel
Abstract: Previous studies about the modulation of the vasculature by CO were performed exclusively in male or sexually immature animals. Understanding the sex differences regarding systemic drug processing and pharmacodynamics is an important feature for safety assessment of drug dosing and efficacy. In this work, we used CORM‐A1 as source of CO to examine the effects of this gasotransmitter on brain perfusion and the sex‐dependent differences. Dynamic contrast‐enhanced imaging (DCE)‐based analysis was used to characterize the properties of CO in the modulation of cerebral vasculature in vivo, in adult C57BL/6 healthy mice. Perfusion of the temporal muscle, maxillary vein and in hippocampus, cortex and striatum was analysed for 108 min following CORM‐A1 administration of 3 or 5 mg/kg. Under control conditions, brain perfusion was lower in females when compared with males. Under CO treatment, females showed a surprisingly overall reduced perfusion compared with controls ( F  = 3.452, p  = .0004), while no major alterations (or even the expected increase) were observed in males. Cortical structures were only modulated in females. A striking female‐dominated vasoconstriction effect was observed in the hippocampus and striatum following administration of CO, in this mixed‐sex cohort. As these two regions are implicated in episodic and procedural memory formation, CO may have a relevant impact in learning and memory. Abstract : CO‐induced vasomodulation is sex‐dependent; CO‐induced vasomodulation is brain region‐dependent; Females are more sensitive to CO therapeutic administration.